Visual analysis of allergic rhinitis in children based on web of science and CiteSpace software - Liu, Fang; Chen, Na; Wang, Rui; Zhang, Lei; Li, Youwei (Frontiers in Pediatrics, 2022)
Background: Recent years, Allergic Rhinitis (AR) in children has caused wide public concern. However, there are few studies concerning the overall trends in AR research in children based on bibliometric analysis. Objective: This study aimed to explore hotspots and emerging trends in AR in children. Methods: Relevant publications were searched from the Web of Science (WOS) Core Collection on December 31, 2021. The searched studies were exported to CiteSpace and Microsoft Excel for further visualized analysis. Results: In total, 649 articles were included. The number of publications related to AR in children has increased steadily in the last 20 years. Giorgio Ciprandi from Italy has the most articles. The leading countries were China and the USA. Guangzhou Medical University in China and Hallym University in Korea were the institutions with the most articles. The high-frequency keywords included allergic rhinitis, asthma, children, prevalence, and symptoms. Pathogenesis, comorbidity, epidemiology, symptoms and therapy of AR in children are research hotspots. Conclusion: Over the past 20 years, research on AR in children has gradually improved. Visualization analysis indicated that pathogenesis, comorbidity, epidemiology, symptoms and therapy are research hotspots, and immunotherapy and severity are probably the main research directions. Keywords: Visualization Analysis; Allergic Rhinitis; Children; Web of Science; CiteSpace